Pelatihan Manajemen Perpustakaan di Sekolah Tinggi Ilmu Ekonomi (STIE) Dwimulya Serang - Ahmad Najiyullah; Ardiyansah Ardiyansah (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
The library management training held at Sekolah Tinggi Ilmu Ekonomi (STIE) Dwimulya Serang was a strategic initiative aimed at enhancing the capacity and competence of library staff in managing modern and effective library services. The program was conducted over two days using a participatory and educational approach that encouraged direct interaction between facilitators and participants. The training covered essential topics such as the fundamentals of library management, collection classification using the Dewey Decimal Classification (DDC) system, circulation service systems, as well as the digitization of collections and the use of the SLiMS (Senayan Library Management System) automation software. Evaluation results indicated a significant improvement in participants' understanding, with post-test scores increasing by an average of 72% compared to pre-test results. Moreover, participants demonstrated their ability to operate SLiMS for digital collection management and showed a better appreciation of the importance of delivering excellent service to library users. Based on the training outcomes, it is recommended that ongoing training programs and sustained institutional policy support be provided to ensure the continuous development of library management practices. Such efforts are expected to transform the library into a modern learning resource center that is responsive to the evolving needs of the academic community and technological advancements.